Exploring the linkages between social media use, self-esteem, and academic performance among nursing students in Saudi Arabia: A descriptive correlational study - Ibrahim, Ibrahim Abdullatif; Mohamed, Mona Hamdy Mostafa; Alenezi, Atallah (Belitung Raya Foundation, Indonesia, 2024)
Background: The prevalence of social media influence in education makes it necessary to investigate how it might affect nursing students’ academic achievement and sense of self. To our knowledge, the associations between academic performance, self-esteem, and social media usage among nursing students from Saudi Arabia remain understudied. Objective: This study aimed to examine the relationships between academic performance, self-esteem, and the utilization of social media platforms by Saudi Arabian nursing students. Methods: This descriptive correlational study employed a convenience sample of 220 nursing students (response rate 95.2%). An online survey with questions about demographics, students’ academic performance, social media usage, and self-esteem was used for data collection from 1 March to May 2023. Pearson correlation coefficients, independent t-tests, Analysis of Variance, and hierarchical regression were used for data analysis. Results: Social media use had an average score of 3.60 ± 0.66, self-esteem was 2.13 ± 0.27, and academic performance was 3.95 ± 0.58. The students’ academic performance related positively to the utilization of social media platforms (r = 0.210, p <0.01). There were statistically positive correlations between academic purpose and social motives domains of utilizing social media and academic performance (r = 0.304, p <0.01; r = 0.208, p <0.01) respectively. The amount of time students spent on social media was not related to their self-esteem (r = 0.047, p >0.05). The students’ self-esteem was unrelated to their academic achievement (r = 0.059, p >0.05). Conclusions: Utilizing social media channels can assist nursing students in improving their academic achievement. Therefore, nursing educators and decision-makers in nursing education have the opportunity to establish collaborative learning environments by integrating social media. This approach aims to improve communication, enhance the learning experience, and ultimately improve the academic achievements of nursing students.